2017
DOI: 10.18632/oncotarget.16518
|View full text |Cite
|
Sign up to set email alerts
|

Novel RNA biomarkers of prostate cancer revealed by RNA-seq analysis of formalin-fixed samples obtained from Russian patients

Abstract: Due to heterogeneous multifocal nature of prostate cancer (PCa), there is currently a lack of biomarkers that stably distinguish it from benign prostatic hyperplasia (BPH), predict clinical outcome and guide the choice of optimal treatment. In this study RNA-seq analysis was applied to formalin-fixed paraffin-embedded (FFPE) tumor and matched normal tissue samples collected from Russian patients with PCa and BPH. We identified 3384 genes differentially expressed (DE) (FDR < 0.05) between tumor tissue of PCa pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…In terms of NEK5 mRNA expression, our observation was fully congruent with the observation made by Nikitina et al in prostate cancer that NEK5 mRNA was displayed to be remarkably higher in cancer tissues relative to normal controls. Regrettably, there has been short of data regarding the biological roles of NEK5 in the study by Nikitina et al Here, we report that NEK5 was an independent prognostic predictor in breast cancer in addition to the significant correlation with tumor size, TNM stage and Ki‐67 status.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In terms of NEK5 mRNA expression, our observation was fully congruent with the observation made by Nikitina et al in prostate cancer that NEK5 mRNA was displayed to be remarkably higher in cancer tissues relative to normal controls. Regrettably, there has been short of data regarding the biological roles of NEK5 in the study by Nikitina et al Here, we report that NEK5 was an independent prognostic predictor in breast cancer in addition to the significant correlation with tumor size, TNM stage and Ki‐67 status.…”
Section: Discussionsupporting
confidence: 92%
“…There having been a paucity of clinical data regarding NEK5 in the context of cancer till now, except for one recent study by Nikitina et al reporting that NEK5 mRNA was found to be over‐expressed in prostate cancer tissues relative to paired normal control tissues from Russian. To understand the NEK5 expression in breast cancer tissues, we performed immunohistochemistry (IHC) on breast cancer tissue microarray consisting of 203 paired cases of breast cancer and its matched normal controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of animal models of sebaceous gland (SG) tumors, Gata6 was found to control sebaceous gland development and cancer . Because GATA6 can be differentially expressed in prostate cancer, GATA6 can be used not only as a candidate biomarker for prostate cancer, but also as a potential therapeutic target . The transcription factor GATA6 is also associated with the occurrence of adrenocortical tumors .…”
Section: Gata6 and Human Cancersmentioning
confidence: 99%
“…102 Because GATA6 can be differentially expressed in prostate cancer, GATA6 can be used not only as a candidate biomarker for prostate cancer, but also as a potential therapeutic target. 103 The transcription factor GATA6 is also associated with the occurrence of adrenocortical tumors. 104,105 As shown in Table 1, the link between the transcription factor GATA6 and other cancers has been summarized.…”
Section: Gata6 and Other Cancersmentioning
confidence: 99%